Modal Sosial Guru untuk Mewujudkan Sekolah Ramah Anak di SMP Dwijendra Denpasar - Dewi, Putu Wulan Purnama; Ranteallo, Ikma Citra; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 3 No 1 (2023): JISSOROT, 2023)
Child-Friendly School Model (Sekolah Ramah Anak - SRA) is mandated by the UN Convention on the Rights of the Child to guarantee the rights, protection, handling, and complaints of student cases. SMP Dwijendra Denpasar is the first private school in Bali that has fulfilled the national SRA principles since 2018. These principles include teacher contributions during preparation, selection, and final assessment by the Ministry of Women's Empowerment and Child Protection. John Field's theory of social capital is an asset that individuals in groups work together toward a common goal. Dwijendra Denpasar Middle School teachers use social capital to optimize student services and facilities. The approach used is qualitative, with descriptive-explanatory research. This study found five social dimensions: (1) cooperation between internal and external stakeholders; (2) trust; (3) networks; (4) norms; and (5) values to maximize service.